2017
DOI: 10.1038/srep44328
|View full text |Cite
|
Sign up to set email alerts
|

Plectin is a novel regulator for apical extrusion of RasV12-transformed cells

Abstract: Several lines of evidence have revealed that newly emerging transformed cells are often eliminated from the epithelium, though the underlying molecular mechanisms of this cancer preventive phenomenon still remain elusive. In this study, using mammalian cell culture systems we have identified plectin, a versatile cytoskeletal linker protein, as a novel regulator for apical extrusion of RasV12-transformed cells. Plectin is accumulated in RasV12 cells when they are surrounded by normal epithelial cells. Similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 30 publications
0
38
0
Order By: Relevance
“…The close proximity of DJs, associated intermediate filaments, and the actomyosin cable may mechanically link the actomyosin cable and desmosomes, either with or without cytoskeletal cross-linkers [12, 34]. A recent study reported a physical coupling between desmoglein 1 and actin via cortactin during skin differentiation, which in turn increases junctional tension in the tissue [12].…”
Section: Resultsmentioning
confidence: 99%
“…The close proximity of DJs, associated intermediate filaments, and the actomyosin cable may mechanically link the actomyosin cable and desmosomes, either with or without cytoskeletal cross-linkers [12, 34]. A recent study reported a physical coupling between desmoglein 1 and actin via cortactin during skin differentiation, which in turn increases junctional tension in the tissue [12].…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeleton reorganization is a fundamental process for the apical extrusion of apoptotic epithelial cells and for cell migration/invasion of metastatic cells 33 - 35 . Prior to extrusion, cells present an overall increase in F-actin levels and a change in actomyosin localization, from basal to apico-cortical deposition 36 .…”
Section: Resultsmentioning
confidence: 99%
“…Fish were maintained at a water temperature of 28 °C. The following fish were used: wild-type AB strain; Et(−26.5Hsa.WT1-gata2:EGFP) cn1 (epi:GFP) 14 ; Tg(myl7:mRFP) 90 , Tg(hsp70l:bmp2b) fr13 and Tg( hsp70l::noggin3 ) fr14 45 , Tg( kdrl::mCherry ) ci5 (from Elke Obeŕs laboratory), Tg( uas::myc-Notch1a-intra ) kca3 , Tg( hsp70l::Gal4 ) kca4 91 ; Tg( fli1a:gal4 ) ubs 3 Tg 55 , Tg( βactin:LifeActin:RFP ) e 2212 Tg 92 , Tg( actb2:myl12.1-mCherry ) e 1954 93 , Tg( BRE-AAVmlp:dmKO2 ) mw 40 46 , Et( krt4:EGFP ) sqet 33 mi 60 A 57 , Tg( Tp1:CreERT2 ) s951 60 , Tg (- 3.5ubb:LOXP-EGFP-LOXP-mCherry ) cz1702 94 Tg(fli1a:eGFP ) 61 and Tg( UAS:mRFP ) 95 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that the paxillin‐plectin‐EPLIN complex is accumulated in RasV12‐ or Src‐transformed cells when they are surrounded by normal epithelial cells, which promote apical elimination of the transformed cells (Kadeer et al, ; Kasai et al, ; Ohoka et al, ). But, knock‐down of EPLIN does not significantly influence accumulation of NMHC‐IIA, and knock‐down of NMHC‐IIA does not affect accumulation of EPLIN (Supporting Information Figure S4a–e).…”
Section: Discussionmentioning
confidence: 99%